Ibn Asyur's Concept of Maqashid Al-Shariah and Its Urgency as a Basis for Contemporary Ijtihad - Ziadul Ulum Wahid; Handoko Budi Prasetiyo; Tutik Hamidah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This paper aims to explore the thoughts of the concept of maqasid shari'ah of Ibn Ashur and its urgency as a basis for conducting ijtihad in the contemporary era. This study uses a library research method with a descriptive and interpretive analysis approach. This study found that Ibn Ashur in the context of understanding maqasid shari'ah offers two methodologies, the first with a text analysis approach and the second by analyzing legal motives. While in the context of ijtihad Ibn Ashur offers five key items that must be understood by a mujtahid, the first is to understand the lafaz in terms of language use and sharia. The second is to make a legal analogy that does not have explicit evidence. The third is to respond to new laws, the fourth is to analyze evidence that appears to be contrasting in terms of zohir and the fifth is ta'abbudi.